Combining an improved political optimizer with convolutional neural networks for accurate anterior cruciate ligament tear detection in sports injuries - Wei Hu; Saeid Razmjooy (Scientific Reports)
Abstract A new technique has been developed to identify ACL tears in sports injuries. This method utilizes a Convolutional Neural Network (CNN) in combination with a modified Political Optimizer (IPO) algorithm, resulting in a major breakthrough in detecting ACL tears. The study provides an innovative approach to detecting this type of injury. The CNN/IPO approach surpasses traditional optimization techniques, ensuring precise and timely detection of ACL tears. This breakthrough has the potential to significantly improve treatment results, enabling clinicians to intervene promptly and effectively, leading to enhanced recovery and rehabilitation for athletes. The integration of the CNN and IPO algorithm provides clinicians with an unparalleled level of accuracy and efficiency in identifying ACL tears, facilitating more precise and tailored treatment strategies for sports-related injuries. The findings have the potential to revolutionize the way medical professionals approach musculoskeletal injuries, enhancing overall well-being and athletic performance. The research’s significance extends beyond sports medicine, illuminating new avenues for the detection and management of ACL tears, and paving the way for advancements in sports injury diagnosis and treatment.